Modeling the elastic behavior of ductile cast iron including anisotropy in the graphite nodules. (1st December 2016) - Andriollo, Tito; Thorborg, Jesper; Hattel, Jesper
Abstracts: This paper presents a micro-mechanical approach to model the intrinsic elastic anisotropy of the graphite particles in ductile iron. Contrary to most of the published works in the field, the constitutive behavior is directly derived on the basis of the nodule characteristic internal structure, composed of graphite platelets arranged into conical sectors. In this way, the large uncertainty traditionally associated with local mechanical measurements of micro-hardness is eliminated. The proposed anisotropic description is validated by simulating the macroscopic ductile iron elastic response by means of a 3D periodic unit cell model. In this respect, an explicit procedure to enforce both periodic displacement and periodic traction boundary conditions in ABAQUS is presented, and the importance of fulfilling the traction continuity conditions at the unit cell boundaries is discussed. It is shown that localized inelastic deformation is likely to develop for loading conditions which can still be considered as elastic at the macroscopic scale. The presence of a weak interface between the graphite and the matrix is also investigated, and it is found to affect the results to a limited extent only.